Morphological characterization of Iris hymenospatha and Iris histrio populations in Iran: implications for conservation and breeding - Rohollahi, Iman; Naji, Amir Mohammad; Stewart, J. Ryan; Kamrani, Rozita (Frontiers in Plant Science, 2024)
Abstract The native populations of Iris hymenospatha and Iris histrio, two endangered bulbous species within the large Iris genus in Iridaceae, are threatened with extinction due to mining and other industrial activities in their natural habitats in Central Asia, including Iran. These species not only have a significant economic impact on the global horticultural industry due to their versatility and attractive phenotypic traits, but also have significant ecological value that necessitates their conservation. In this study, we examined the morphological and functional diversity between individuals within these two species, which exhibit high tolerance to environmental stresses. Our study examined 10 populations of I. hymenospatha and two populations of I. histrio based on bulb, flower, and leaf characteristics throughout Iran. We recognized a gradation of five different leaf shapes among I. hymenospatha populations with significant differences between some populations, including ‘Arak-Khomain’ and ‘Arak-Gerdo’. The ‘Jaro’, ‘Natanz-Karkas,’ ‘Ardestan-Taleghan,’ ‘Arak-Rahjerd,’ ‘Arak-Gerdo,’ ‘Ganjnameh,’ and ‘Abas-Abad’ populations of I. hymenospatha displayed maximal values in leaf width, stem diameter under flower, crown diameter, flower number, leaf number and bulb diameter. The I. histrio ‘Velian’ population had significantly larger flower size, longer stem length, larger style width, longer flowering date, and higher plant height compared to the ‘Ganjnameh’ population of I. histrio. Such characteristics of both species make them remarkable ornamental plants. Our study also revealed that I. hymenospatha populations grow on different soils and elevations and have the ability to adapt to different growing conditions. Given the threats they face, conservation through horticultural selection and propagation offers a viable conservation strategy for both species. This approach not only preserves the genetic diversity of these species, but also enables their further contribution to the horticultural industry.